The Role of Task Technology Fit to Enhance Student Satisfaction Towards Blended Learning in Chengdu, China - Li, Wenbo (Scholar: Human Sciences, 2024)
Purpose: Blended learning had become a popular educational approach that mixed the characteristics of face-to-face lectures and online learning in the digital age. This research aimed to examine the factors of task technology fit, confirmation, cognitive presence, teaching presence, social presence, and learner-instructors interaction to impact blended learning satisfaction of college students in Chengdu, China. The research model demonstrates relationships between key varaibles. Research design and methodology: This research applied the quantitative method and questionnaire as instruments to survey 500 students, who majored in art and design subjects. Before distributing the questionnaires, Item-Objective Congruence (IOC) and a pilot test of Cronbach’s Alpha were used to test validity and reliability. Data was analyzed by utilizing Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to validate the model’s goodness of fit and confirm the causal relationship among variables for hypothesis testing.. Results: The main findings revealed that confirmation, cognitive presence, social presence, and learner-instructors interaction significantly influenced satisfaction with blended learning, except task technology fit and teaching presence. Cognitive presence and learner-instructor interaction has strong and significant role to enhance students’ satisfaction with hybrid learning. Conclusions: The study has found that the research conceptual model could predict and explain how the factors impact blended learning satisfaction.